Influence in Economics and Aging - Pavel Jelnov; Yoram Weiss (Global Labor Organization (GLO), 2021)
We study the relationship between age and influence in a closed group of leading economists. We consider, as a measure of influence, monthly RePEc rankings and address the dynamics of rankings within the top group as a function of age. We find that the rankings peak at age 60 or 30 years after Ph.D. graduation. Differently from other leaders, current and future Nobel laureates do not experience deterioration of the rankings if their works and citations are discounted by recursive impact factor, and their ranking with respect to the breadth of citations across fields improves at old age.
Keywords: J24; 330; aging; citations; influence; Nobel; research productivity